Hạn chế tài chính và cấu trúc kỳ hạn nợ tại các doanh nghiệp Việt Nam - Nguyễn Thanh, Liêm; Nguyễn Thị, Cành; Nguyễn Công, Thành (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study examines corporate debt maturity of listed firms with different levels of financial constraints in Vietnam. Using quantile regression, we show that the coefficients of determinants of corporate debt maturity structure change their signs and significance at different quantiles of debt maturity structure. Besides, firms with high levels of financial constraints are more likely to be subject to liquidity risk and information asymmetry, while their financially unconstrained peers have better conditions to address the above two market imperfections. Both firm groups manifest strong interest in curbing agency cost associated with long debt maturity structure. These results suggests that for firms in developing markets such as Vietnam, those with low financial constraints tend to be the ones that react more actively to take advantage of proper corporate debt maturity structures. Employing Oaxaca-Blinder decomposition technique, the study points out that the difference in debt maturity structure between the two firm groups is caused chiefly by the factors of tangible assets, tax rate, and credit quality.
Keywords: Corporate debt maturity structure; Quantile regression; Oaxaca-Blinder decomposition